The Modeling and Simulation of High-Speed Continuous and Discontinuous Chip Formation in the Machining of AISI 4340 Steel - Araujo, Eric (My University, 2000)
Throughout engineering history, metal cutting technology has been pushed to keep pace with the development of stronger and more difficult to cut materials. With the advent of robust machining technology, the finish cutting of hardened materials at high speeds and extreme conditions has become possible. As we push the thresholds of our technology, the need for a deep understanding of the processes at work in metal cutting in order to predict limit states has become clear. The prediction of machining processes began with models that described the problem qualitatively. The principals and assumptions used within these laid the foundations for further theoretically based empirical models. With the advent of computationally based numerical modeling, predictive modeling of metal cutting processes using elasto-plastic based simulation has brought a new perspective to the field. The development of finite element modeling techniques capable of modeling both continuous and discontinuous chip formation has become a subject of considerable research effort. The present work focuses on the study and development of explicit transient finite element techniques used to simulate the orthogonal machining of hardened steel under various cutting conditions producing both continuous and discontinuous chips. Metal cutting involves a diversity of complex physical phenomenon such as large strain and strain rate plasticity, high temperature contact and friction conditions, material failure, adiabatic shear localization, and thermo-mechnically based deformation. The numerical modeling of these processes in orthogonal machining operations is the primary focus of this work. The effects of cutting conditions on chip morphology and the finished workpiece are investigated and resulting phenomenon are explained in terms of numerically based stress analysis. Benchmarking comparisons with literature and commercial modeling software simulations are made and quantified in terms of strains, temperatures, residual stresses, and the various components of stress. Future directions and issues are outlined and recommendations are made. Solution stability of the finite element solver applied to machining was quite low due to the lack of an adaptive remeshing scheme and deficiencies in the contact algorithm. Thermal mechanical coupling and remeshing are currently being implemented. Future avenues include methods of surface generation without volumetric losses. the application of friction based on wear data, and the application of machining simulations to oblique three-dimensional cutting operations.
Keywords: chip; formation; continuous; discontinuous; aisi 4340 steel; model; simulation